Pendampingan Terhadap Koperasi UMKM Tajur Halang Makmur Untuk Meningkatkan Omset Penjualan - Enok Tuti Alawiah; Dinin Setyorini; H Hasanudin (LPPM STIKOM Tunas Bangsa, 2023)
The Tajur Halang Makmur UMKM Cooperative has members from the MSME forum from the Tajur Halang District MSME Forum, Bogor Regency. The majority of business actors have businesses in the culinary and handicraft sectors. Currently, production is still carried out on a household business scale using simple production equipment so product quantities are still limited. Currently, business actors have problems in terms of product marketing, packaging design, making financial reports and after-sales service to customers. Mentoring activities are carried out to provide training to MSMEs in terms of making packaging label designs, making financial reports and broader product marketing training. The aim of the activity is to increase the sales turnover of MSME business actors so that they can continue their business with an increased turnover. The activity method is carried out in the form of face-to-face training which is divided into four activity sessions. Training activities were carried out in the Tajur Halang District Hall. The results of the activity show that partners' skills and knowledge have increased in terms of design creation, product marketing and preparation of financial reports.